Motivation for seeking employment in the light of unemployment measures - Zatoń, Tomasz (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
The aim of the paper is an empirical analysis of factors affecting the scale of the divergences between the levels of registered and LFS unemployment rates in Poland in the years 2005–2014. The set of variables used for explaining this phenomenon includes potential sources of motivation (of economic, social and psychological origin) of the unemployed persons actively seeking employment. The research method used was econometric analysis of panel data across voivodships. The results showed some significant factors having impact on the discrepancies in differently measured unemployment rates. They represent: the level of income and wages, numer of economic entities, degree of urbanization, as well as education and professional experience of the unemployed, access to benefits and the responsibilities associated with family caring. The study confirms that the difference in the levels of alternative measures of unemployment is largely due to a different definition of commitment of the unemployed persons in seeking employment.